2019
DOI: 10.1021/acsami.9b17108
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Free Selective Deposition of Lithium Metal into Tough Graphene Framework for Stable Lithium Metal Anode

Abstract: Graphene has been wildly used as a host to suppress dendrite growth to stabilize the lithium metal anode. However, the high overpotential of lithium deposition on pure graphene has to be lowered by doping or employing precious metals. Additionally, the soft nature of graphene rendered itself to aggregate, consequently squeezing room for lithium accommodation. Herein, a tough graphene framework composed of 3D periodic hollow spheres was reported as a free-standing host to stabilize lithium metal anodes. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
(40 reference statements)
0
29
0
Order By: Relevance
“…[84] 3D-structured self-supported electrode materials can be also constructed from GNSs by a broad range of methods, and hence, several unique structures were suggested. [85][86][87][88] Li et al reported that heavy metal-based current collectors can be substituted with relatively lightweight GNS-based frameworks that have more lithiophilic sites and hierarchically porous structures and can be obtained by a Cu foam-assisted template method. [85] Pan et al used uniform polystyrene spheres to prepare 3D graphene frameworks comprising 3D periodic hollow spheres with interconnected 3D ion-diffusion channels by a template method (Figure 4g).…”
Section: Design Of 3d Carbon Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…[84] 3D-structured self-supported electrode materials can be also constructed from GNSs by a broad range of methods, and hence, several unique structures were suggested. [85][86][87][88] Li et al reported that heavy metal-based current collectors can be substituted with relatively lightweight GNS-based frameworks that have more lithiophilic sites and hierarchically porous structures and can be obtained by a Cu foam-assisted template method. [85] Pan et al used uniform polystyrene spheres to prepare 3D graphene frameworks comprising 3D periodic hollow spheres with interconnected 3D ion-diffusion channels by a template method (Figure 4g).…”
Section: Design Of 3d Carbon Structuresmentioning
confidence: 99%
“…[85] Pan et al used uniform polystyrene spheres to prepare 3D graphene frameworks comprising 3D periodic hollow spheres with interconnected 3D ion-diffusion channels by a template method (Figure 4g). [86] As a hybrid carbon structure, a carbon nanofiberstabilized graphene aerogel film host was prepared from electrospun carbon nanofibers and graphene oxide using chemical reduction and a solution casting method. [87] In addition, vertically grown edge-rich GNSs were fabricated on SiO 2 nanowire@carbon nanofiber networks with a density of 0.012 g cm −3 by low-pressure CVD at 5 kPa.…”
Section: Design Of 3d Carbon Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same capacity and different current densities, compared with other Li-metal batteries with 3D graphene current collectors, GCN exhibited advantages in terms of CE and cycling life (Fig. 4d and Table S2) [40][41][42][43][44][45][46][47][48][49][50][51]. At 5.0 mA cm −2 in ether electrolyte, the GCN electrode remained stable even after 100 cycles, while the rGO electrode exhibited fluctuating performance after 40 cycles.…”
Section: Resultsmentioning
confidence: 89%